"Anti-electrostatic" halogen bonding in solution. Issue 23 (19th May 2021) - Loy, Cody; Holthoff, Jana M.; Weiss, Robert; Huber, Stefan M.; Rosokha, Sergiy V.
Abstract : Spontaneous formation of "anti-electrostatic" complexes in solution demonstrates that halogen bonding can be sufficiently strong to overcome anion–anion repulsion when the latter is attenuated by the polar medium. Abstract : Halogen-bonded (XB) complexes between halide anions and a cyclopropenylium-based anionic XB donor were characterized in solution for the first time. Spontaneous formation of such complexes confirms that halogen bonding is sufficiently strong to overcome electrostatic repulsion between two anions. The formation constants of such "anti-electrostatic" associations are comparable to those formed by halides with neutral halogenated electrophiles. However, while the latter usually show charge-transfer absorption bands, the UV-Vis spectra of the anion–anion complexes examined herein are determined by the electronic excitations within the XB donor. The identification of XB anion–anion complexes substantially extends the range of the feasible XB systems, and it provides vital information for the discussion of the nature of this interaction.